2002
DOI: 10.1002/dev.10074
|View full text |Cite
|
Sign up to set email alerts
|

Visual search for high‐level configural differences as well as low‐level critical features is highly efficient early in childhood

Abstract: Visual search, or the ability to locate a single target from a field of distractors, is used as a means of assessing the capacity of the visual system with regard to the detection of low-level stimulus dimensions such as color, line orientation, and other specific perceptual features and higher level characteristics such as three-dimensional (3-D) orientation implied by pictorial cues to depth or occlusion. Target-distractor differences of importance to the visual system result in rapid (and possibly preattent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
2
5
1
Order By: Relevance
“…Based on additive factors logic, comparing search RTs and simple detection RTs allows for the isolation of effects due to cognitive development and those of sensory-motor maturation. As already observed in previous studies, search RTs decreased with increasing age (Trick and Enns, 1998; Gerhardstein et al, 2001; Gerhardstein and Rovee-Collier, 2002; Adler and Orprecio, 2006; Donnelly et al, 2007). In the present study, significant RT decreases were observed between the groups of 6- and 8-year-olds, 8- and 10-year-olds, 10- and 12-year-olds, and 14- and 16-year-olds.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Based on additive factors logic, comparing search RTs and simple detection RTs allows for the isolation of effects due to cognitive development and those of sensory-motor maturation. As already observed in previous studies, search RTs decreased with increasing age (Trick and Enns, 1998; Gerhardstein et al, 2001; Gerhardstein and Rovee-Collier, 2002; Adler and Orprecio, 2006; Donnelly et al, 2007). In the present study, significant RT decreases were observed between the groups of 6- and 8-year-olds, 8- and 10-year-olds, 10- and 12-year-olds, and 14- and 16-year-olds.…”
Section: Discussionsupporting
confidence: 82%
“…In line with the results of previous studies (Trick and Enns, 1998; Gerhardstein et al, 2001; Gerhardstein and Rovee-Collier, 2002; Donnelly et al, 2007) RTs were expected to decrease with increasing age. However, as suggested by Donnelly et al (2007), if RTs are affected by newly developing cognitive skills (such as the ability to rely target detection responses on the presence of salience peaks rather than the matches between features and templates), RTs, in addition to sensory-motor maturation, are also expected to be modulated by the different cognitive processes invoked to solve the search task in participants aged 6-years relative to participants aged 8 and older.…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations